2019
DOI: 10.1002/cm.21543
|View full text |Cite
|
Sign up to set email alerts
|

Scattered podosomes and podosomes associated with the sealing zone architecture in cultured osteoclasts revealed by cell shearing, quick freezing, and platinum‐replica electron microscopy

Abstract: Osteoclasts (OCs) can adhere to a variety of substrate surfaces by highly dynamic actin‐based cytoskeletal structures termed podosomes. This tight attachment is established by a sealing zone (SZ), which is made of interconnected individual podosomes. Compared with scattered podosomes in various cell types, the architecture of the SZ is still unclear. Especially, ultrastructural studies on the details of the cytoskeletal structure of an OC have been challenging, because the high density of filaments in their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
(111 reference statements)
2
4
0
Order By: Relevance
“…After 3 days, osteoclasts efficiently degraded bone, as shown by scanning electron microscopy (SEM) observations (Figure 2A). SEM acquisitions of unroofed cells confirmed that the sealing zones formed by human osteoclasts are composed of individual F-actin cores (Figure 2B-B'), similarly to what was shown in osteoclasts differentiated from the mouse cell line RAW 264.7 or harvested from rabbit long bones 8,10 . These cores were nested in a dense network of actin filaments, and appeared connected to their neighbors by filaments running parallel to the substrate (Figure 2B'', arrowheads).…”
Section: Nanoscale Organization Of Actin Cores In the Sealing Zonesupporting
confidence: 74%
See 1 more Smart Citation
“…After 3 days, osteoclasts efficiently degraded bone, as shown by scanning electron microscopy (SEM) observations (Figure 2A). SEM acquisitions of unroofed cells confirmed that the sealing zones formed by human osteoclasts are composed of individual F-actin cores (Figure 2B-B'), similarly to what was shown in osteoclasts differentiated from the mouse cell line RAW 264.7 or harvested from rabbit long bones 8,10 . These cores were nested in a dense network of actin filaments, and appeared connected to their neighbors by filaments running parallel to the substrate (Figure 2B'', arrowheads).…”
Section: Nanoscale Organization Of Actin Cores In the Sealing Zonesupporting
confidence: 74%
“…First described as a subcellular entity made of electron dense material and apparently deprived of any organelle, thus resulting in first denomination as the "clear zone", the sealing zone was then revealed to consist in a dense accumulation of actin filaments forming a circular shape surrounding the resorption lacuna [5][6][7] . Examination with scanning electron microscopy (SEM) of cells removed of their basal membrane brought to light the peculiar arrangement of actin filaments within this structure, and particularly unveiled the existence of a dense network of podosomes composing this structure [8][9][10] . Podosomes are adhesion structures that are generally scattered in macrophages and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison to the podosome’s exquisite organization 50 , 51 , recent ultrastructure analysis by platinum replica electron microscopy revealed a rather rudimentary invadopodia architecture, consisting of a ~200–300 nm array of Arp2/3 branched actin filaments with their (+)-ends facing the plasma membrane/collagen fiber contact zone 38 ( Figure 2 ). Despite a simple actin meshwork organization, invadopodia can efficiently push collagen fibers away using energy from Arp2/3 complex-dependent actin polymerization 38 .…”
Section: Podosome Vs Invadopodia Organization: Beauty and The Beastmentioning
confidence: 99%
“…First described as a subcellular entity made of electron dense material and apparently deprived of any organelle, thus resulting in first denomination as the ‘clear zone’, the sealing zone was then revealed to consist in a dense accumulation of actin filaments forming a circular shape surrounding the resorption lacuna ( Zambonin-Zallone et al, 1988 ; Kanehisa et al, 1990 ; Teti et al, 1991 ; King and Holtrop, 1975 ; Han et al, 2019 ). Examination with scanning electron microscopy (SEM) of cells removed of their basal membrane brought to light the peculiar arrangement of actin filaments within this structure, and particularly unveiled the existence of a dense network of podosomes composing this structure ( Luxenburg et al, 2007 ; Akisaka and Yoshida, 2015 ; Akisaka and Yoshida, 2019 ). Podosomes are adhesion structures that are generally scattered in macrophages and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it appears paramount to develop higher resolution microscopy techniques compatible with observation on bone substrates. This could yield valuable information concerning the spatial distribution of major actin-binding proteins within the sealing zone, otherwise only arduously accessible via electron microscopy and correlative microscopy Luxenburg et al, 2007 ; Akisaka and Yoshida, 2015 ; Akisaka and Yoshida, 2019 ; Akisaka and Yoshida, 2016 ; Geblinger et al, 2009 . Additionally, observation of the sealing zone internal dynamics would provide substantial hints to understand the sealing ability of such a structure.…”
Section: Introductionmentioning
confidence: 99%